(untitled) (Research, Society and Development, 2022)
Objective: to outline the clinical and epidemiological profile of patients admitted to a public children’s hospital in Teresina - Piauí diagnosed with COVID-19. Methodology: This is a descriptive, retrospective and quantitative study, carried out through the analysis of medical records of patients diagnosed with COVID-19, hospitalized and admitted to the COVID-19 sector of a children’s hospital located in the city of Teresina-PI. The medical records of patients of both sexes, aged up to 15 years and who tested positive for the disease during the year 2020, were included. Results: The total sample of this study consisted of 96 medical records of patients who met the established criteria, being the majority were male (55,2%), living in the countryside of the state of Piauí (50,0%) and mean age of 4,.4 ± 4, 2. The main manifestations found were fever (79,2%), respiratory distress (56.3%), cough (52,1%), vomiting (29,2%), runny nose (25,0%), diarrhea (17,7%), sore throat (12,5%), headache (8,3%), nasal congestion (7,3%) and sneezing (2,1%). Conclusion: It is possible to conclude that the profile of pediatric patients hospitalized with COVID-19 is composed mainly of patients belonging to early childhood (0 to 5 years old). Most of them also had at least one preexisting disease or condition or concomitant with the period of hospitalization for SARS-CoV-2, without the presence of neuropsychomotor disorders and were not using continuous medication. As this is a disease that has not yet had all its mechanisms clarified, it is important to emphasize the need for further studies.